Методология оценки аспектов научно-технического и инженерного обеспечения государства - Gudauskas, Renaldas (Knygotyra, 2024)
There is no fully accepted conception of the basis on which librarians and bibliographers should be educated. There is no theoretical solution in the USSR or in the world. However, the history of higher education for librarians and bibliographers is closely connected with universities. The author of the article substantiates the merits of education at universities, reveals the possibilities of some of the Soviet universities to prepare library and bibliography specialists. The results of this research should help in solving the problem of diversity in types and forms of higher education for librarians and bibliographers.